Inflammatory Markers and Genetic Polymorphisms in Workers Exposed to Flour Dust. Issue 5 (May 2016) - Marraccini, Paolo; Cantone, Laura; Barretta, Francesco; Marsili, Chiara; Leghissa, Paolo; Santini, Marisa; Elli, Francesca; Bertazzi, Pier A.; Previdi, Mario
Abstract : Objective: The aim of this study is to evaluate inflammatory markers and pro-inflammatory CD14 and Toll-like Receptor 4 (TLR4) polymorphisms in workers exposed to flour dust. Methods: Polymorphisms in TLR4 and CD14 were identified in our study population of 167 workers that included 63 healthy subjects (HS), 45 atopic subjects (A), and 59 subjects diagnosed clinically with occupational asthma/rhinitis (OAR). Endpoint measures in this study included fractional exhaled nitric oxide and serum concentrations of interleukin IL-6, IL-8, and tumor necrosis factor-alpha (TNF-α). Results: We identified a polymorphism in CD14 (rs2569190) that may be differentially expressed ( P = 0.06). IL-6 concentrations in the serum were significantly higher in the A and OAR groups ( P < 0.01) than in subjects in the HS group, while IL-8 concentrations were significantly elevated only in the OAR group ( P < 0.01). Interestingly, TNF-α concentrations in the OAR group were significantly reduced when compared with subjects in the HS group ( P < 0.01). Conclusion: Cytokines are likely a defensive response in atopic and healthy workers. A protective genotype is hypothesized for occupational asthma.